What is the best strategy for one-lung ventilation during thoracic surgery? - Grande, Bastian; Ganter, Michael T. (Journal of Thoracic Disease; Vol 10, No 12 (December 30, 2018): Journal of Thoracic Disease, 2018)
Today, one-lung ventilation (OLV) is a highly established and accepted technique to facilitate thoracic surgical procedures, for example a lung lobectomy. In the perioperative period, lung function may critically worsen and impair patient’s outcome. On the one hand, the mechanical trauma of the operated lung poses a challenge for the postoperative recovery; on the other hand, a ventilator-induced lung injury can have deleterious consequences (1,2). Atelectases, inflammation, edematous change of the lung and partial over-inflation present a risk for postoperative hypoxemia and hypercapnia. Careful and evidence-based perioperative ventilation strategies are the starting point for a successful, low-complication perioperative pulmonary outcome.